2017
DOI: 10.1021/acs.bioconjchem.6b00530
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Hydrophilic Auristatin Derivatives for Use in Antibody Drug Conjugates

Abstract: Antibody drug conjugates offer a targeted cancer treatment for the delivery of potent cytotoxic drugs. Derivatives of the natural product dolastatin 10 containing pyridines and other basic amines were examined with the objective of determining if a more hydrophilic auristatin derivative would be potent enough for use as part of an ADC. This may be advantageous if a less hydrophobic drug makes a better ADC. A pyridine derivative, monomethyl auristatin PYE, showed the greatest potency when tested in vivo. While … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 37 publications
0
36
0
Order By: Relevance
“…Many research groups have studied auristatins with a focus mostly on the P1 and P5 subunits and these modifications have been extensively reviewed 16,50) (Fig. 3).…”
Section: Study Of Auristatin Derivativesmentioning
confidence: 99%
See 3 more Smart Citations
“…Many research groups have studied auristatins with a focus mostly on the P1 and P5 subunits and these modifications have been extensively reviewed 16,50) (Fig. 3).…”
Section: Study Of Auristatin Derivativesmentioning
confidence: 99%
“…The MMAPYE (8) and aniline 17 were evaluated in vivo (data not shown in this paper). We identified that MMAPYE (8) was the payload with the best activity and the least toxicity in vivo 16) (17 showed signs of toxicity at the 4 mg/kg dose, pronounced body weight loss). It was successfully attached to a variety of linkers then conjugated to trastuzumab for evaluation as an ADC (Fig.…”
Section: Evaluation Of In Vivo Efficacy Of Adc With Mmapye (8) As Paymentioning
confidence: 99%
See 2 more Smart Citations
“…We chose to use the cathepsin B cleavable linker valine-citrulline for its improved effect over a non-cleavable linker (data not shown). We picked the microtubule inhibitor MMAF as the toxic payload due to its previously characterized strong potency in ADC formats and improved solubility compared to MMAE 25 . Both ADCs showed high potency in a HER2-positive breast cancer cell line, BT474-M1, compared to either trastuzumab alone or an aGFP Fab control (Fig.…”
Section: Enhancing Stability Of Oxaziridine Conjugatesmentioning
confidence: 99%